PENGARUH INDEPENDENSI, GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI DAN PEMAHAMAN GOOD GOVERNANCE TERHADAP KINERJA AUDITOR PEMERINTAH ( Studi Empiris Pada BPKP Perwakilan Jawa Tengah ) - Widh, Saputro i Nugroho; Setyawati, Erma (Benefit: Jurnal Manajemen dan Bisnis, 2015)
This study aims to understand the effect of independence, leadership style, organizational commitment, and an understanding of good governance on the performance of government auditors. Data obtained by distributing questionnaires to government auditors who worked in Central Java BPK Representative Office. Questionnaires were spread to 50 respondents, only 40 respondents that the data can be analyzed and processed research data analysis using multi-linear regression analysis with SPSS Windows version 16.0 program. This study consists of dependent and independent variables. The dependent variable is the performance of government auditors, and the independent variables is independence, leadership style, organizational commitment, and understanding of good governance. The results show that the independence, leadership style, organizational commitment is not a positive influence on the performance of government auditors. Simultaneous test results that independence, leadership style, organizational commitment does not have a positive influence on the performance of collective government auditors. Only variables of good governance has a positive effect on the performance of collective government auditors.